Effects of the smart board on students' achievement in moral education - Ling, L.W. (Institute of Electrical and Electronics Engineers Inc., 2014)
In this era of globalization, Malaysia is recognized as one of the pioneers in introducing Smart board among schools in the region of Southeast Asia. The aim of this study is to investigate whether the use of Smart board in Moral Education improved students' achievement. The study examined the achievement of the Form 4 students in a school in the Kinta district in Perak Darul Ridzuan, Malaysia comparing scores between students whose teachers used the Smart board for instruction and those whose teachers did not. A total number of 50 students are involved in the study. They are divided into two experimental and control groups. A pre-test and post-test was conducted. The findings show slightly higher achievement among students in the Smart board group as compared to students not using it, thus exhibiting the advantage of using the Smart board instruction. The resultant dataset after comparing a pre-post test supports the idea that students whose teachers used the Smart board with a new Moral Education smart board courseware show greater post-test to pre-test achievement gains than students whose teachers did not use the SB. Â© 2014 IEEE.